A Splendid Gift from the Earth: The Origins and Impact of the Avermectins (Nobel Lecture)1. Issue 35 (20th July 2016) - Ōmura, Satoshi
Abstract : Japanese soil was the origin of one of the most important drugs of the world: ivermectin. No other drug has such importance for the health of millions of people, particularly in the poor regions of the world. The discovery of the parent compounds of the avermectines is described first hand by S. Ōmura.